2014
DOI: 10.4166/kjg.2014.63.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Acute Obstructive Cholangitis Complicated by Tumor Migration after Transarterial Chemoembolization: A Case Report and Literature Review

Abstract: Intraductal tumor invasion of hepatocellular carcinoma (HCC) is considered rare. Transarterial chemoembolization (TACE) is effective for tumor thrombus of HCC in the bile duct. However, a few cases of obstructive jaundice caused by migration of a tumor fragment after TACE have recently been reported. The aim of this study was to identify factors that affect tumor migration after TACE. At this writing, a review of the medical literature disclosed seven reported cases of biliary obstruction caused by migration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…42 Spontaneous liver rupture after DEB-TACE has also been reported. 43 These ADE do not appear to be specific to DEB-TACE, because they have also been reported after cTACE, [44][45][46][47] and the affected patients are usually older and experience multiple preoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…42 Spontaneous liver rupture after DEB-TACE has also been reported. 43 These ADE do not appear to be specific to DEB-TACE, because they have also been reported after cTACE, [44][45][46][47] and the affected patients are usually older and experience multiple preoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] However, there has been no study of their long-term clinical outcomes. In addition, according to Kim et al, 10 asymptomatic patients whose tumors spontaneously pass into the gastrointestinal tract can be kept under observation.…”
Section: Discussionmentioning
confidence: 99%
“…10 Ductal invasion with intraductal tumor ingrowth in HCC is one of the main reasons for obstructive jaundice in HCC patients. In almost all cases with intraductal tumor fragment migration after TACE, CT scans performed before TACE show evidence of bile duct invasion, such as irregularly dilated ducts passing through the tumor or intraductal protrusion of the tumor, 12 and Park et al 12 suggested that intraductal invasion would be a major predisposing factor to tumor migration after TACE. Rarely, it may also occur in patients without bile duct invasion because TACE induces marked ischemia in the tumor vascular bed and adjacent biliary tree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migration of intraductal tumour ingrowth to the distal common bile duct, causing obstructive jaundice, rarely occurs following chemoembolization of HCCs with bile duct invasion, which is the so-called 'sloughing' of an intraductal tumour ingrowth [9][10][11][12][13][14][15][16][17][18]. The clinical course of this event remains poorly documented.…”
Section: Introductionmentioning
confidence: 96%